New Power Sharing Control for Inverter-Dominated Microgrid Based on Impedance Match Concept - Herong Gu; Deyu Wang; Hong Shen; Wei Zhao; Xiaoqiang Guo (The Scientific World Journal)
Power flow control is one of the most important issues for operating the inverter-dominated autonomous microgrid. A technical challenge is how to achieve the accurate active/reactive power sharing of inverters. P-F and Q-V droop control schemes have been widely used for power sharing in the past decades. But they suffer from the poor power sharing in the presence of unequal line impedance. In order to solve the problem, a comprehensive analysis of the power droop control is presented, and a new droop control based on the impedance match concept is proposed in this paper. In addition, the design guidelines of control coefficients and virtual impedance are provided. Finally, the performance evaluation is carried out, and the evaluation results verify the effectiveness of the proposed method.